Bilateral maxillectomy via mid-facial degloving approach in an extensive case of post-Coronavirus disease invasive fungal sinusitis - Singh, Sampath Kumar; Gayatri, Kuthadi; Reddy Yalaka, Mounika (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
Coronavirus disease associated invasive fungal sinusitis has affected many and several have succumbed to the disease during the second wave of COVID-19 pandemic. Mucormycosis is a rare, opportunistic, fulminant, angioinvasive fungal infection caused by Rhizopus species of the order Mucorales. It mainly affects immunocompromised individuals, predisposed by diabetes mellitus, corticosteroids, immunosuppressive therapy, haematological malignancies and organ transplantation. We reported here a case of a 45 years old male with past history of Coronavirus disease, presenting with symptoms of invasive fungal sinusitis. With this case we emphasised on use of an alternate approach for bilateral total maxillectomy via midfacial degloving approach instead of a classical external Weber Ferguesen incision in extensive cases with several associated co-morbidities. Mid facial degloving approach is a combination of intraoral and intranasal incisions made to access the midface without any external incision. This approach is advantageous in comparatively having less complication rate, less morbidity and excellent cosmetic outcome.